Epidemiological Characterization of a Fourth Wave of Pandemic A/H1N1 Influenza in Mexico, Winter 2011–2012: Age Shift and Severity - Borja-Aburto, Víctor H. (2012)
BACKGROUND AND AIMS: A substantial recrudescent wave of pandemic influenza A/H1N1 affected the Mexican population from December 1, 2011–March 20, 2012 following a 2-year period of sporadic transmission. METHODS: We analyzed demographic and geographic data on all hospitalizations with severe acute respiratory infection (SARI) and laboratory-confirmed A/H1N1 influenza, and inpatient deaths, from a large prospective surveillance system maintained by a Mexican social security medical system during April 1, 2009– March 20, 2012. We also estimated the reproduction number (R) based on the growth rate of the daily case incidence by date of symptoms onset. RESULTS: A total of 7569 SARI hospitalizations and 443 in-patient deaths (5.9%) were reported between December 1, 2011, and March 20, 2012 (1115 A/H1N1-positive inpatients and 154 A/H1N1-positive deaths). The proportion of laboratory-confirmed A/H1N1 hospitalizations and deaths was higher among subjects ≥60 years of age (χ(2) test, p <0.0001) and lower among younger age groups (χ(2) test, p <0.04) for the 2011–2012 pandemic wave compared to the earlier waves in 2009. The reproduction number of the winter 2011–2012 wave in central Mexico was estimated at 1.2–1.3, similar to that reported for the fall 2009 wave, but lower than that of spring 2009. CONCLUSIONS: We documented a substantial increase in the number of SARI hospitalizations during the period December 2011–March 2012 and an older age distribution of laboratory-confirmed A/H1N1 influenza hospitalizations and deaths relative to 2009 A/H1N1 pandemic patterns. The gradual change in the age distribution of A/H1N1 infections in the post-pandemic period is consistent with a build-up of immunity among younger populations.